2021
DOI: 10.1111/cts.13065
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP3A5 polymorphisms and parathyroid hormone with blood level of tacrolimus in patients with end‐stage renal disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“… 2 In a rat model, secondary hyperparathyroidism (SHPT) decreased CYP3A activity, whereas SHPT therapy with cinacalcet restored it. 3 Consistent with this finding, but in contrast to Suzuki et al, 4 a positive correlation between iPTH level and TAC concentration was found in the present study by Tanaka et al 1 and also a study by Hirata et al 5 …”
Section: Figuresupporting
confidence: 88%
See 2 more Smart Citations
“… 2 In a rat model, secondary hyperparathyroidism (SHPT) decreased CYP3A activity, whereas SHPT therapy with cinacalcet restored it. 3 Consistent with this finding, but in contrast to Suzuki et al, 4 a positive correlation between iPTH level and TAC concentration was found in the present study by Tanaka et al 1 and also a study by Hirata et al 5 …”
Section: Figuresupporting
confidence: 88%
“…We appreciate our colleagues’ findings on the interesting association between CYP3A5 polymorphism, serum intact‐PTH (iPTH) levels, and tacrolimus (TAC) trough. 1 CYP3A4 and CYPA5 are important determinants of TAC metabolism, which can be described simply by the concentration‐to‐dose (C/D) ratio. 2 In a rat model, secondary hyperparathyroidism (SHPT) decreased CYP3A activity, whereas SHPT therapy with cinacalcet restored it.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We welcome Westphal et al’s response to our recent publication. As they point out, our 1 and Hirata et al 2 previous retrospective studies have very small sample sizes of 48 and 12 patients, respectively. In our paper, time points of measurements for tacrolimus (TAC) and intact parathyroid hormone (iPTH) were not standardized, and logistic regression analysis did not partition TAC concentration/dose (per body weight) ratio (C/D) into a binary dependent variable.…”
mentioning
confidence: 57%
“…In addition, our previous study found that the correlation coefficient of both factors increased from r = 0.305 to 0.428 by excluding these patients. 1 However, kidney transplant recipients take multiple medications for primary and comorbidities, some of which have CYP3A inhibitory activity. Thus, we also consider that iPTH levels may not correlate with TAC C/D in the entire patients who undergo kidney transplantation.…”
mentioning
confidence: 99%